(untitled) (Indonesian Economic Justice Review, 2024)
This paper explores the role of Indonesia’s rapidly growing digital economy in promoting economic justice, with a focus on the tech sector’s impact on job creation, income distribution, and access to resources. The digital economy, powered by innovations in e-commerce, fintech, and digital platforms, has expanded opportunities for entrepreneurs and workers, particularly in urban areas. However, this paper critically assesses whether these opportunities are equitably distributed across the population, especially for marginalized groups such as women, rural communities, and low-income populations. The case study centers on the development of major digital platforms in Indonesia, such as Gojek, Tokopedia, and Bukalapak, and examines their contribution to job creation, economic inclusion, and local development. The study also considers the risks of digital inequality, including issues related to digital literacy, access to technology, and the precarious nature of gig economy jobs within the tech sector. By analyzing government policies, corporate practices, and community engagement in the digital space, the paper identifies challenges and opportunities for enhancing economic justice through digital innovation. The findings suggest that while the digital economy has the potential to drive inclusive growth, additional policies are required to ensure equitable access and prevent the deepening of digital divides. The paper concludes with recommendations for fostering digital inclusion, ensuring fair wages, and protecting workers’ rights in the tech sector.